In vitro transcription of a cloned mouse ribosomal RNA gene. - Mishima, Y (1981)
An in vitro transcription system which utilizes cloned mouse ribosomal RNA gene (rDNA) fragments and a mouse cell extract has been developed. RNA polymerases I is apparently responsible for this transcription as evidenced by the complete resistance to a high concentration (200 micrograms/ml) of alpha-amanitin. Run-off products obtained with three different truncated rDNA fragments indicated that RNA was transcribed from a unique site of rDNA. The S1 nuclease protection mapping of the in vitro product and of in vivo 45S RNA confirmed this site, indicating that, in this in vitro system, transcription of rDNA started from the same site as in vivo. This site is located at several hundred nucleotides upstream from the putative initiation site reported by us (1) and by others (2). Some sequence homology surrounding this region was noted among mouse, Xenopus laevis and Drosophila melanogaster. The data also suggest that some processing of the primary transcript occurs in this in vitro system.